Deconvolution of E/Z tetrahydroisoquinoline amide rotamers and conformers from a marine-derived Streptomyces strain. Issue 52 (27th December 2018) - Nepomuceno, Vanessa M.; Kim, Hiyoung; Ding, Yuanqing; Liu, Hongbing; Sadek, Mark; Ferreira, Daneel; Omarsdottir, Sesselja; Murphy, Brian T.
Abstract: A collaborative program to discover new specialized metabolites from aquatic environments of Iceland led to the deconvolution of tetrahydroisoquinoline amide E/Z rotamers [( E/Z )- N -acetyl-MY336-a;1 ] and conformers produced by a Streptomyces sp. All structures were elucidated by NMR and MS analysis, and interpretation of electronic circular dichroism (ECD) data. ECD and optical rotation (OR) simulations permitted the unequivocal assignment of the absolute configuration of compound1 and provided an important example of delineating the spectroscopic contributions of equilibrating rotamers and boat/chair conformers of a common natural product scaffold. Graphical abstract: